Improving the sensitivity of amino-silanized sensors using self-structured silane layers: Application to fluorescence pH measurement - Rutjaphan Kateklum (2018)
© 2017 Elsevier B.V. We investigated the possibility to grow molecularly porous amino-silane layers on glass-like substrates. The goal of this work is to show that it is possible to substantially increase the sensitivity of a fluorescence sensor by adjusting the functionalization strategy. Two methods are studied, one using APTMS only and another one using both APTMS and APDMS. We show that, using the second method, sensor sensitivity is improved by a factor of about 5. In order to demonstrate this, we applied the technique to the grafting of fluorescein in order to build a fluorescence pH sensor.